(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This paper examined a phonological study of consonants and vowels phonemic merger in Hausa. The main objective of this research is to examine how phonological and morphological rules trigger phonemic merger of certain consonants and vowels phonemes in particular phonetic environments of a word as phonetic and phonemic entity, on the assumption that, phonological and morphological rules relate an underlying structure to its phonetic representation. The study employed generative phonological framework in the analysis of the data so that we can establish the set of rules that describe the changes of the underlying structure when they occur in speech. Also, for the data collection an ethnographic communication method is adopted. The findings of the research discovered three phonological processes that motivate consonants and vowels phonemic merger in Hausa. The identified phonological processes are: palatalization, rhotacization and deletion motivating phonemic merger. In addition, it is noted that phonemic merger is a rule-governed process because, we have clearly seen how a series of cumulative Hausa phonological and morphological rules operate on the underlying forms, and transform them into surface forms in realizing a phonemic merger in Hausa.